2017
DOI: 10.18632/oncotarget.20728
|View full text |Cite
|
Sign up to set email alerts
|

EV20-Sap, a novel anti-HER-3 antibody-drug conjugate, displays promising antitumor activity in melanoma

Abstract: Melanoma is the most biologically aggressive skin cancer of well established constitutive and induced resistance to pharmacological treatment. Despite the recent progresses in immunotherapies, many advanced metastatic melanoma patients still face a significant mortality risk. The aggressive nature of this disease sustains an urgent need for more successful, effective drugs. HER-3 - one of the four member of the tyrosin kinase epidermal growth factor receptors (EGFRs) family- is frequently overexpressed in soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…EV20-Sap treatment results in significant reduction of pulmonary metastasis in murine melanoma model. 158 …”
Section: Other Anti-her3 Targeted Therapiesmentioning
confidence: 99%
“…EV20-Sap treatment results in significant reduction of pulmonary metastasis in murine melanoma model. 158 …”
Section: Other Anti-her3 Targeted Therapiesmentioning
confidence: 99%
“…Small-molecule inhibitors that bind to the ATPbinding pocket of ERBB3 (TX1-85-1, TX-121-1) also effectively promote ERBB3 degradation, interfere with ERBB3 heterodimerization, and inhibit ERBB3-dependent pathways. 92 Anti-ERBB3 antibodies conjugated to cytotoxic drugs, such as saponin, 93 monomethyl auristatin F, 94 and the topoisomerase I inhibitor DXd (exatecan derivative for ADC), 95 have shown promise in mouse cancer models and human cancer cell lines. Finally, vaccines using peptides derived from ERBB3 exert antitumor effects against breast and pancreatic cancers.…”
Section: Approaches Used To Develop New Therapeutic Agents Targeting mentioning
confidence: 99%
“…41 To date, uncleavable saporin-or MMAF-conjugated HER3-specific ADCs have been preclinically proposed as monotherapy for melanoma. 42,43 The anti-HER3 antibody patritumab conjugated to a topoisomerase I inhibitor via a cleavable linker is currently tested in phase I/II trials for patients with metastatic breast cancer 44 and has been preclinically demonstrated to be an effective treatment for EGFR-mutant NSCLC with acquired resistance to EGFR TKIs. 45 However, no HER3-specific ADC linked to a cleavable MMAE has been proposed for the radiosensitization of pancreatic tumors.…”
Section: Discussionmentioning
confidence: 99%